The world of the Bahá'í Faith - Stockman, Robert H. 1953- (London New York Routledge, Taylor & Francis Group, 2022)
Leadership and authoritative texts -- Theology -- Humanity -- Society -- Contemporary Bahá'í community -- History and spread of the Bahá'í community.
"The World of the Bahá'í Faith is an outstanding guide to the Bahá'í Faith and its culture in all its geographical and historical diversity. Written by a distinguished team of international contributors, this volume explores the origin of this religion and contains substantial thematic articles on the living experience of the global Bahá'í community. The volume is organised into six distinct sections: Leadership and Authoritative Texts-Theology-Humanity-Society-Contemporary Bahá'í Community-History and Spread of the Bahá'í Community"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bahai Faith